Obesity resistance and enhanced glucose metabolismin mice transplanted with white adipose tissue lackingacyl CoA:diacylglycerol acyltransferase 1 - Chen, Hubert C. (American Society for Clinical Investigation, 2003)
Recent studies have identified the white adipose tissue (WAT) as an important endocrine organ that regulates energy and glucose metabolism via a number of secreted factors. Mice lacking acyl CoA:diacylglycerol acyltransferase 1 (DGAT1), a key enzyme in mammalian triglyceride synthesis, are protected against diet-induced obesity and glucose intolerance because of increased energy expenditure and enhanced insulin sensitivity. Because DGAT1 is highly expressed in WAT, we hypothesized that DGAT1 deficiency affects the expression of adipocyte-derived factors that regulate energy and glucose metabolism. Here we show that the transplantation of DGAT1-deficient WAT decreases adiposity and enhances glucose disposal in wild-type mice. Analysis of DGAT1-deficient WAT revealed a twofold increase in the expression of adiponectin, a molecule that enhances fatty acid oxidation and insulin sensitivity, and this increase may account in part for the transplantation-induced metabolic changes. Our results highlight the importance of the endocrine function of WAT and suggest that an alteration in this function contributes to the increased energy expenditure and insulin sensitivity in DGAT1-deficient mice.